Analisis Konsep Green Marketing pada Pengembangan Pariwisata Pesisir yang Berkelanjutan - Wiyanti, Wiyanti; Ratri Wikaningtyas (Lembaga Pengembangan Kinerja Dosen, 2026)
This study stems from the growing awareness of the importance of sustainable coastal tourism management through the application of the green marketing concept. Increasing tourism activities in coastal areas often create environmental pressure, thus requiring marketing strategies that balance ecological and social aspects. In the context of regional development, green marketing is expected to serve as a strategic approach to create economic value without compromising the sustainability of natural resources. The purpose of this study is to analyze the extent to which green marketing contributes to the development of sustainable coastal tourism in Tegal Regency, Tegal City, and Brebes Regency. The research employs a qualitative analytical approach involving 200 informants, including tourism managers, local communities, and tourists. Data were collected through observation, interviews, and documentation, and analyzed thematically. The results show an average green marketing implementation level of 74.3%, with the highest performance found in waste management and eco-friendly product innovation. Overall, green marketing contributes positively to enhancing destination image and environmental awareness among tourism stakeholders.